Effect of dry and steam heating on the functional and bread baking properties of yellow pea and navy bean flours. Issue 6 (29th September 2019) - Bourré, Lindsay; Young, Gina; Hill, Heather; Fraser, Shona; Borsuk, Yulia; Sarkar, Ashok; Sopiwnyk, Elaine; Jones, Stuart; Dyck, Adam; Malcolmson, Linda
Abstract: Background and objectives: Although there is growing interest in partially replacing wheat flour with pulse flours in bread, the flavor of pulse flours can limit their use. Heat treating pulse flours, with and without the addition of steam, was examined to determine whether the flavor of split yellow pea flour (SYPF) and whole navy bean flour (WNBF) could be improved without altering flour functionality and bread baking properties. Findings: Significant temperature × steam interactions were found for most flour parameters including pasting properties, water absorption capacity (WAC), starch damage, and color. Protein, starch, and flour particle size were altered as were pasting and farinograph properties of the pulse/wheat flour blends. Differences in specific volume, color, and C‐cell properties were more evident in the breads made with the treated WNBFs likely due to the different bread formulation used and the presence of hull in the flour. Conclusions: Processing the SYPF and the WNBF at 120 and 140°C with steam improved the aroma and flavor of the bread while maintaining good flour functionality and bread baking properties. Significance and novelty: Heating treating pulse flours with the addition of steam successfully reduced the objectionable aroma and flavor characteristics associated with SYPF and WNBF. Eliminating undesirable aroma and flavor properties provides a greater opportunity for the inclusion of pulse flours in foods to enhance their nutritional properties.